Performance of Asphalt Mixture Incorporated Encapsulated Cigarette Butts as Bitumen Modifier - Ameen, H. AL-A. Nader; P. J., Ramadhansyah (Penerbit UMP, 2022)
Cigarette butts are non-biodegradable waste, and the difficulties in dealing with cigarette waste is a big concern for communities and environmental groups all over the world. In past years, cigarette butts has been increasingly used on flexible pavement and has become one of the causes that increases pavement strength and reduces environmental challenges. Environmental factors are external influences that affect the performance of flexible pavements. These include snow, chemicals, water, and ageing issues. The aim of this research is to evaluate the mechanical and physical properties of asphalt mixture incorporating encapsulated cigarette butts. Asphalt concrete has a number of problems, including rutting, moisture removal, and binder drain. The use of asphalt is restricted due to high temperatures that cause rutting cracking of the asphalt or coating layer. Therefore, it is necessary to modify asphalt and improve its quality with less affects to environment. In this research, experiments were carried out to compare two types of asphalt which are unmodified asphalt and modified asphalt mixture. For modified asphalt, various percentages of encapsulated cigarette butts were added to the mixtures. The additive used was encapsulated cigarette butts with increment 0%, 0.2%, 1% and 3% for the bitumen and 0%, 5%, 10% and 15% for asphalt mixture. Penetration test, softening point, ductility test, penetration index, los angeles (LA) abrasion test, marshall tests, indirect tensile strength test and dynamic creep test were performed. The findings of the studies performed in this project reveal that varying the percentages of cigarette butts in the asphalt concrete mixture obviously differs in the mechanical and physical characteristics of asphalt mixture. As a result, the addition of CBs to AC resulted in a different abrasion loss value when compared to unmodified AC. At 10% CBs put into the asphalt mixture, the abrasion loss was chosen as the most advantageous level for increasing the performance of AC mixture. Based on the results of the mechanical and physical tests we can infer that 5% of CBs is the best percentage of cigarette butts to add in asphalt mixture. So this study proved that cigarette butts to be an effective material is used as an addition to asphalt binder because it improves performance by increasing paving strength and stiffness.